The social and emotional experiences of black lesbian couples in Seshego Township, Limpopo Province - Maotoana, M. R. (University of Limpopo, 2019)
South African has constitutional protection for the human rights of all its citizens. However, black lesbians in South Africa suffer physical, emotional and psychological abuse. This qualitative study aimed to elicit the social and emotional experiences of black lesbians living, as same-sex partners, in a township setting. The design of the study was exploratory in nature and used a purposive sample of ten couples (twenty women). The investigation was underpinned by Social domain theory (SDT) which allowed for an understanding of the judgements people make in different social settings. Semi-structured interviews were conducted with each couple in order to collect data. The data were analysed using thematic content analysis (TCA) which gleaned ten themes namely, age and sexual orientation, suicide, education, lack of support, hate crimes, substance abuse, stigma, mental health, parenting and discrimination. In the discussion it was found that these themes echoed those in other local and international studies. However, corrective rape is peculiar to South Africa and was experienced by some participants in the study. In one case a brother, with the mother’s support raped his sister repeatedly. This took place in a country which has a progressive constitution and laws. Social norms in the township allows black lesbian couples to suffer this type of abuse and have daily experiences of discrimination and stigmatisation. Recommendations included a quantitative more far reaching study (as well as longitudinal studies) and more workshops and campaigns spreading knowledge about sexuality.
Thesis (Ph. D. (Psychology)) --University of Limpopo, 2019
Keywords: Social experiences; Emotional experiences; Black lesbian couples; Seshego Township; Lesbians, Black; Emotion recognition